Numerical simulation and parameterisation of rail–wheel normal contact. (April 2017) - Cuperus, Jacobus L; Venter, Gerhard
This investigation aims to find empirical equations that describe the rail–wheel normal (frictionless) contact characteristics. These equations can then be used to determine an equivalent Hertzian load to account for normal contact in the finite element analyses mandated by the Transnet RS/ME/SP/008 specification, without explicitly simulating the contact between two bodies. The standard is similar to UIC 510-5 and does not consider tangential contact. The normal contact problem is solved for the test case using nonlinear finite element methods as well as the boundary element method. Material plasticity was also investigated in finite element analyses with limited effect for contact away from the flange area. The data from boundary element analyses were fitted to a power law equation for each contact parameter. The equivalent Hertzian contact produced with the empirical equations is able to predict the normal contact parameters relatively accurately, producing a maximum error of 9.6% (excluding one area with a geometric anomaly).